2016
DOI: 10.3847/1538-4357/833/1/39
|View full text |Cite
|
Sign up to set email alerts
|

Muse Gas Flow and Wind (Megaflow). I. First Muse Results on Background Quasars*

Abstract: The physical properties of galactic winds are one of the keys to understand galaxy formation and evolution. These properties can be constrained thanks to background quasar lines of sight (LOS) passing near star-forming galaxies (SFGs). We present the first results of the MusE GAs FLOw and Wind survey obtained from two quasar fields, which have eight Mg II absorbers of which three have rest equivalent width greater than 0.8 Å. With the new Multi Unit Spectroscopic Explorer (MUSE) spectrograph on the Very Large … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
124
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(132 citation statements)
references
References 78 publications
6
124
2
Order By: Relevance
“…Furthermore, relative gas and galaxy kinematics show that low ions are kinematically connected to their host galaxy by aligning with their rotation curves and being modelled well by accreting+corotating gas (Steidel et al 2002;Kacprzak et al 2010Kacprzak et al , 2011aHo et al 2017;Martin et al 2019;Zabl et al 2019). On the other hand, minor axis gas also seems to be well modelled by outflowing gas (Bouché et al 2012;Gauthier & Chen 2012;Schroetter et al 2016). Finally, the metallicity distribution of LLS and pLLS appears bimodal, which also suggests that outflows and accretion are dominant phenomena within the CGM (Wotta et al 2016.…”
Section: Fig 5-same As Left Panel Ofmentioning
confidence: 96%
“…Furthermore, relative gas and galaxy kinematics show that low ions are kinematically connected to their host galaxy by aligning with their rotation curves and being modelled well by accreting+corotating gas (Steidel et al 2002;Kacprzak et al 2010Kacprzak et al , 2011aHo et al 2017;Martin et al 2019;Zabl et al 2019). On the other hand, minor axis gas also seems to be well modelled by outflowing gas (Bouché et al 2012;Gauthier & Chen 2012;Schroetter et al 2016). Finally, the metallicity distribution of LLS and pLLS appears bimodal, which also suggests that outflows and accretion are dominant phenomena within the CGM (Wotta et al 2016.…”
Section: Fig 5-same As Left Panel Ofmentioning
confidence: 96%
“…Cuts in both impact parameter and velocity difference between absorber and galaxy differ between published MUSE absorber studies, making the comparison of results not straightforward. MusE GAs FLOw and WInd (MEGAFLOW), a MUSE survey of Mg ii absorbers, (Schroetter et al 2016) allows for a 1000 km s −1 velocity difference between the galaxy and the absorber, and in case of multiple detections, the lowest-impact-parameter object is selected. Quasar Sightline And Galaxy Evolution (QSAGE), an OVI absorption oriented MUSE program (Bielby et al 2019), supported by a larger impact parameter coverage with HST grisms, uses a tight limit of 400 km s −1 (expected outflow velocity).…”
Section: Absorbers Are Associated With Multiple Galaxiesmentioning
confidence: 99%
“…Integral-field spectroscopy with instruments like SIN-FONI (Eisenhauer et al 2003), MUSE (Bacon et al 2006) or OSIRIS (Larkin et al 2006), make it possible to obtain spectra of many sources in the field-of-view and efficiently classify galaxies associated with absorbers. Combined with highresolution UV spectroscopy of quasars, these studies have revealed relevant features interpreted as galactic outflows (Schroetter et al 2016;Rahmani et al 2018b;Schroetter et al 2019), warped accretion discs (Rahmani et al 2018a) and galactic fountains (Bouché et al 2016). Alongside the detection of kinematic traces of gas inflows and outflows, new studies detected multiple galaxies associated with one absorber (Bielby et al 2017;Péroux et al 2017;Klitsch et al 2018;Nielsen et al 2018;Péroux et al 2019;Muzahid et al 2019).…”
mentioning
confidence: 99%
“…In particular, thanks to its large 1 arcmin 2 field of view, its extended wavelength coverage in the optical, and its exquisite sensitivity, MUSE has become the ideal instrument for studies of the CGM of galaxies in quasar fields (e.g. Schroetter et al 2016;Fumagalli et al 2016Fumagalli et al , 2017bPéroux et al 2017;Bielby et al 2017;Klitsch et al 2018;Chen et al 2019).…”
mentioning
confidence: 99%